(untitled) (Research, Society and Development, 2022)
The purpose of the study is to systematically review about alveolar recruitment maneuvers followed by mechanical ventilation with PEEP guided by electrical impedance tomography (EIT) in laparoscopic bariatric surgery. Metodology: The primary outcomes were: regional pulmonary ventilation (regional impedance variation), end-expiratory lung impedance, and end-expiratory lung volume. Results: The survey identified three eligible studies. The sample consisted of 136 participants of both genders. The alveolar recruitment maneuver (ARM) was performed through the mechanical ventilator and using the EIT in the patient’s chest. The studies showed moderate to high risk of bias, and the quality of the evidence was classified as very low quality due to the methodological limitations found and absence of directionality. Conclusion: ARM with PEEP guided by EIT does not significantly improve the respiratory system mechanics in the intraoperative period in obese patients undergoing laparoscopic bariatric surgery.